Learning to teach with cinema: creation and pedagogical possibilities in the teaching path (Revista Internacional de Formação de Professores, 2023)
The essay points to possibilities of reinvention of teaching through cinema and audiovisual language as a pedagogical device, observing the teaching path through learning to teach, crossing elements of the audiovisual language present in the pedagogy practices of Inventar com a Diferença, a film project, education and human rights created by researchers from the Fluminense Federal University. It addresses reflections on recognizing oneself and reinventing oneself as a teacher. Brings the clipping of communication and audiovisual when meeting with education. It observes aspects related to the path taken in teaching life, permeated by the term “training ecosystem”, contextualizing the feedback tool applied in education.
Keywords: Movie theater. Teaching. Learn. Feedback. Reinvention.